2019
DOI: 10.1038/s41371-019-0254-3
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and 5-year mortality in patients with peripheral arterial disease

Abstract: Arterial stiffness (AS) is a risk factor which coexist in high-risk populations including peripheral arterial disease (PAD). However, the prognostic impact of arterial stiffness in PAD remains to be defined. We investigated whether aortic Pulse Wave Velocity (aPWV) and Augmentation index normalized to 75 beats/min (Aix @75HR) predict total mortality (all-cause and cardiovascular mortality) in patients with PAD. In 231 PAD with ABI ≤0.9 at rest or with a positive Treadmill test performed on the borderline group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
15
1
3
Order By: Relevance
“…NT-proBNP concentrations (expressed as decimal logarithms) were also significant predictors of cIMT and P2/P1 in multivariate analysis. While cIMT is a well-established marker of cardiovascular disease, P2/P1 and its derivative—the augmentation index shows a weaker correlation with hard-end points than the gold standard of arterial stiffness—aortic pulse wave velocity [ 36 , 37 ]. Little is known about pathophysiological relations between intimal and medial thickening and the heart.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP concentrations (expressed as decimal logarithms) were also significant predictors of cIMT and P2/P1 in multivariate analysis. While cIMT is a well-established marker of cardiovascular disease, P2/P1 and its derivative—the augmentation index shows a weaker correlation with hard-end points than the gold standard of arterial stiffness—aortic pulse wave velocity [ 36 , 37 ]. Little is known about pathophysiological relations between intimal and medial thickening and the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown that the development of arterial stiffness may be prior to hypertension (Celik et al, 2017; Kaess et al, 2012), which causes left ventricular remodeling (Ohyama et al, 2016; Zieman et al, 2005), it is well established that hypertension, associated or not with aging, leads to an increased arterial stiffness (Morgan et al, 2014; Rode et al, 2020), assessed by pulse wave velocity (PWV). In fact, arterial stiffness has been recognized as an independent predictor of all‐cause mortality in population with several diseases including hypertension (DuPont et al, 2019; Scandale et al, 2020), and understanding the mechanisms involved in vascular stiffness is an emerging target to treat hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Being a systemic atherosclerotic disease, it is frequently associated with an unacceptably high incidence of cardiovascular events, including new onset angina, coronary artery bypass grafting, nonfatal or fatal myocardial infarction, and congestive heart failure 137 . PAD also associated with an increase in overall all-cause and cardiac mortality 138 . The relationship between PAD and depression appears be bi-directional 139,140 .…”
Section: Depression and Peripheral Artery Diseasementioning
confidence: 93%